2018
DOI: 10.7567/jjap.57.08re03
|View full text |Cite
|
Sign up to set email alerts
|

Charge traps in lead-halide perovskites with different grain sizes

Abstract: It is crucially required to understand charge traps in CH3NH3PbI3 perovskites, which severely affect charge recombination mechanism and hence have a critical impact on photovoltaic performance. Herein, we studied the photoexcited dynamics of CH3NH3PbI3 perovskites with different grain sizes by measuring intensity dependence of time-resolved photoluminescence. As a result, we found that the photoluminescence (PL) decay for all the samples can be well analyzed by bimolecular radiative recombination and trap-assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…As a result, the charge carriers in the FA 0.5 MA 0.4 Cs 0.1 PbBr 3 perovskite flow without many barriers. 36 On the other hand, in the MA 0.9 Cs 0.1 PbBr 3 perovskite, the flow of charge carriers is more restricted and the possibility of accumulation of charge carriers in the perovskite material is more, resulting in a higher R ct .…”
Section: Resultsmentioning
confidence: 99%
“…As a result, the charge carriers in the FA 0.5 MA 0.4 Cs 0.1 PbBr 3 perovskite flow without many barriers. 36 On the other hand, in the MA 0.9 Cs 0.1 PbBr 3 perovskite, the flow of charge carriers is more restricted and the possibility of accumulation of charge carriers in the perovskite material is more, resulting in a higher R ct .…”
Section: Resultsmentioning
confidence: 99%
“…The limiting factors for rapid charge separation and slow charge recombination are determined by how many trap states, defects and dislocations of the carriers throughout the perovskite film in bulk crystals or in the boundaries of the crystals . There have been reported that the bigger size of the crystals gives the better overall device performance due to a better crystal growth control to increase the charge transport rate and to decrease the electron‐hole recombination rate . In contrast, Don et al .…”
Section: Figurementioning
confidence: 99%